2011
DOI: 10.5551/jat.5686
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness is Strongly Associated with Insulin Resistance in Chinese —A Population-Based Study (Taichung Community Health Study, TCHS)

Abstract: Chih-Te Ho and Cheng-Chieh Lin contributed equally to this work.Aim: Few studies have investigated the association between insulin resistance and arterial stiffness in Chinese. We aimed to investigate this relationship in a population-based study of middle-aged Chinese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 26 publications
3
23
0
1
Order By: Relevance
“…To our knowledge, this is the first cohort study to show the impact of ADIPOQ G276T on prognoses and to suggest a mechanism of how ADIPOQ G276T affects the onset of stroke. Previous studies reported the correlation between PWV and silent cerebrovascular diseases 38) or insulin resistance 39) , and our results supported and provided new insight into these correlations.…”
Section: Discussionsupporting
confidence: 77%
“…To our knowledge, this is the first cohort study to show the impact of ADIPOQ G276T on prognoses and to suggest a mechanism of how ADIPOQ G276T affects the onset of stroke. Previous studies reported the correlation between PWV and silent cerebrovascular diseases 38) or insulin resistance 39) , and our results supported and provided new insight into these correlations.…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, some studies in non-diabetic and diabetic population show that IR increases significantly the risk for cardiovascular disease, independently of all classic and several nontraditional risk factors (Bonora et al, 2002(Bonora et al, , 2007Caravaca et al, 2010;Ho, Lin, Hsu, et al, 2011;Sciacqua et al, 2013;Shinohara et al, 2002;Tsuchiya, Nakayama, Iwashima, et al, 2007). Accumulating evidence suggests that patients with IR, even CKD patientsBanerjee, 2011, have impaired vascular function, leading to the development of atherosclerosis and consequently increased cardiovascular events Banerjee, 2011;Britton, Mukamal, Ix, et al, 2012;Ho et al, 2011;Sciacqua et al, 2013;Shinohara et al, 2002;Tsuchiya et al, 2007) since there are findings that support a variety of anti-atherogenic effect of insulin witch might be blunted by IR (Bonora et al, 2007). An et al (2012) showed that IR is an independent predictor for atherosclerosis plaque progression in patients with coronary heart disease in both diabetic and non-diabetic population.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, insulin resistance and/or metabolic syndrome have been consistently associated with increased arterial stiffness in various ethnicities and in both genders. [3235]…”
Section: Discussionmentioning
confidence: 99%